Electrophysiological Indicators of the Age-Related Deterioration in the Sensitivity to Auditory Duration Deviance - Nowak, Kamila; Oron, Anna; Szymaszek, Aneta; Leminen, Miika; Näätänen, Risto; Szelag, Elzbieta (Frontiers in Aging Neuroscience, 2016)
The present study investigates age-related changes in duration discrimination in millisecond time domain. We tested young (N = 20, mean age = 24.5, SD = 2.97) and elderly (N = 20, mean age = 65.2, SD = 2.94) subjects using the Mismatch Negativity (MMN) paradigm. White-noise bursts of two different durations (50 ms and 10 ms) were presented in 2 oddball blocks. In one block (Increment Condition), the repetitive sequence of 10 ms standards was interspersed by occasional 50 ms deviants. In the Decrement Condition, the roles of the two stimuli were reversed. We analyzed the P1-N1 complex, MMN and P3a and found the effect of age for all these components. Moreover, the impact of stimulus presentation condition (increment/decrement) was observed for MMN and P3a. Our results confirmed the previous evidence for deteriorated duration discrimination in elderly people. Additionally, we found that this effect may be influenced by procedural factors.